Penentuan Harga Pokok Produksi Pagar Menggunakan Metode Biaya Pesanan Pada CV. Ahsan Jaya mandiri - Yusuf, Cahyo Muhammad (EKONOMIA, 2020)
Calculation of cost of production by using the order cost method is right method to use in industry or businesses in the field of assembly, most of which are carried out an order basis because the process of recording costs still relative simple. The formulation of the problem of this research is whether the cost producingfences determined by CV. Ahsan Jaya Mandiri is lower than the cost of production according to the order cost method. The purpose of this study is to find out information on the difference in cost of production according to the company and the cost of production according to the order cost method and compares the price of production based on the order cost method with the cost of production according to CV. Ahsan Jaya Mandiri. The theoretical basis used in this research is cost accounting which focuses on calculating the cost of production of fences on CV. Ahsan Jaya Mandiri. The research hypothesis is the cost of production carried out by CV. Ahsan Jaya Mandiri is lower than the cost of production according to the order cost method. The analytical tool used is depreciation rate of fixed assets, the loading of factory overhead costs to the product of the calculation of the cost of production and the card price of the order. The results showed that the calculation of the cost of fence according to CV. Ahsan Jaya Mandiri is lower than the difference between the order cost method due to CV. Ahsan Jaya Mandiri does not account for indirect labor costs and a portion of factory overhead costs into the production costs of fences.Â